Proceedings of the Ocean Drilling Program, 160 Scientific Results 1998
DOI: 10.2973/odp.proc.sr.160.005.1998
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous nannofossils in the basal Zanclean of the Eastern Mediterranean Sea: remarks on paleoceanography and sapropel formation

Abstract: This paper presents the results of a study on nannofossil assemblages in the uppermost Messinian and basal Zanclean sediments recovered from Ocean Drilling Program (ODP) Holes 969B (south of Crete) and 967A (north of the Eratosthenes Seamount) located in the Eastern Mediterranean Sea. Focus of the research is on (1) the micropaleontological signature of the basically nonmarine facies of the uppermost Messinian interval; (2) the correlation of the Messinian/Zanclean boundary outside the Mediterranean by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 45 publications
(80 reference statements)
2
38
0
Order By: Relevance
“…Biostratigraphic events for global correlations are mainly provided by calcareous nannofossils: the Discoaster quinqueramus LO, dated at 5.537 Ma, and the first occurrence of Ceratolithus acutus dated at 5.37 Ma in the equatorial Atlantic slightly predating the Messinian/Zanclean boundary (Backman & Raffi, 1997). The disappearance of Triquetrorhabdulus rugosus was recorded in Mediterranean deep-sea cores (Castradori, 1998;Di Stefano et al, 1996) and in the equatorial Atlantic (Backman & Raffi, 1997) at 5.23 Ma. Planktonic foraminiferal events, such as the Sphaeroidinellopsis spp.…”
Section: Zancleanmentioning
confidence: 99%
See 2 more Smart Citations
“…Biostratigraphic events for global correlations are mainly provided by calcareous nannofossils: the Discoaster quinqueramus LO, dated at 5.537 Ma, and the first occurrence of Ceratolithus acutus dated at 5.37 Ma in the equatorial Atlantic slightly predating the Messinian/Zanclean boundary (Backman & Raffi, 1997). The disappearance of Triquetrorhabdulus rugosus was recorded in Mediterranean deep-sea cores (Castradori, 1998;Di Stefano et al, 1996) and in the equatorial Atlantic (Backman & Raffi, 1997) at 5.23 Ma. Planktonic foraminiferal events, such as the Sphaeroidinellopsis spp.…”
Section: Zancleanmentioning
confidence: 99%
“…The Gelasian stage was proposed by Rio et al (1994;1998) to represent the uppermost and third interval of the Pliocene Series, corresponding to the strong climatic deterioration due to orbitally controlled glacial cycles in the Northern Hemisphere. The stage was named from the Greek name of the town of Gela, near to the Monte S. Nicola section where the Gelasian GSSP was established.…”
Section: The Gelasian Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Higher values of F. profunda have been previously documented in other Pliocene sapropels (Zanclean age) from the Mediterranean region (Castradori 1998), connecting the increased abundance of the species with the development of DCM. Similarly, Negri et al (2003) observed the same pattern of a well-developed DCM favouring F. profunda during the deposition of Pleistocene sapropels.…”
Section: Zanclean/piacenzian Sapropelic Layers: Paleoceanographic-palmentioning
confidence: 86%
“…Calcareous nannofossils are one of the most important pelagic sediment micro-components (Müller 1985;De Kaenel and Villa 1996;Castradori 1998;Negri et al 1999a, b;Negri and Villa 2000;Vázque et al 2000), used mainly for biostratigraphy and paleoceanographic reconstructions. Calcareous nannofossil biostratigraphy historically provides first-order age control in many outcrops and cores.…”
Section: Introductionmentioning
confidence: 99%